SENTRA KERAJINAN KULIT SEBAGAI KAWASAN WISATA INDUSTRI DI KABUPATEN MAGETAN - Zarra Primita Aryana; Sumaryoto Sumaryoto; Leny Pramesti (ARSITEKTURA, 2016)
The development of Leather Crafting Center “Sawo Street” in Magetan Regency is supported by the increasing numbers of tourists who visit the place, the increasing numbers of leather craft showrooms, the availability of development area, great amount of raw materials, and the local crafters as the embryo of this industrial tourism. Therefore, the objective of this design is about achieving an area design which provides the facilities for shopping tourism activities, especially for leather crafting products, facilitate industrial tourism activities and training activities for the crafters into the building design that expresses local area architecture as the land mark of Magetan Regency. The problem of the design is about how the finishing of mass system of the buildings in the area and the expression of buildings with local architecture can be interpreted into the area design of Leather Crafting Center “Sawo Street” in Magetan Regency. The method used in this study is architecture design method. The achieved result is the design of leather crafting shopping center, industrial tourism, and training center area in the form of supporting building facilities in a tourism area in order to optimize the function of Leather Crafting Center “Sawo Street” in Magetan Regency as industrial tourism area.